Stripe rust effector Pst9653 interferes with subcellular distributions of catalase TaCAT3 to facilitate susceptibility-involved ROS scavenging in wheat - Wei, Xiaobo (The New phytologist, 2025)
© 2025 The Author(s). New Phytologist © 2025 New Phytologist Foundation.